Wind turbine monitoring system using wireless sensor networks - Bhuiyan, MM; Billah, MM (Journal of the Bangladesh Agricultural University, 2014)
Wireless sensor networks can be used in wind farm monitoring where periodic data collection about the sound generated inside the farm as well as detection and monitoring of faulty wind turbines is necessary. Periodic sound data collection requires reliability while faults detection necessitates timeliness. Simultaneous data gathering and faults monitoring was not well studied in literature. This paper proposed a system model that worked on homogeneous data gathering Wireless sensor networks deployed in wind farms. When a wind turbine became faulty, a cluster with a different transmission channel around that wind turbine was formed and both periodic sound data gathering and faults monitoring were performed at the same time. The proposed model had a novel routing strategy with a built-in congestion control technique to provide timely delivery of faults data. Experimental results show that the proposed method performed better than known similar techniques in terms of reliable data gathering and reliable timely faults monitoring. Due to lower number of high power transmissions, the proposed method had 8% to 17% higher success rate of regular system and 94% of accuracy at the fault monitoring. In terms of timely faults detection and notification, this method had a comparative performance to the existing methods. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19936 J. Bangladesh Agril. Univ. 11(2): 321-330, 2013